Container cover material

JP7640337B2Active Publication Date: 2025-03-05TOYO ALUMINIUM KK
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021062040
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-31
Publication Date
2025-03-05
Estimated Expiration
2041-03-31

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、優れた付着防止性を発揮しつつ、付着防止層の下方に位置する文字、図柄等の表示内容を視認することができる蓋材を提供することができる。特に、本発明の蓋材では、透明性樹脂層及び付着防止層の構成が透明性を発揮できる構成となっているので、文字、図柄等が透明性樹脂層、ホットメルト樹脂層及び付着防止層で覆われた状態になっているにもかかわらず、文字、図柄等の表示内容を正確に視認し、あるいは読み取ることができる。それと同時に、付着防止層が最外層(最表面)に配置されているので、高い付着防止効果(撥水性)を発揮することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640337000002
    Figure 0007640337000002
  • Figure 0007640337000003
    Figure 0007640337000003
  • Figure 0007640337000004
    Figure 0007640337000004
Patent Text Reader

Abstract

To provide a lid material capable of visually recognizing display contents such as a character and a pattern that are positioned below an adhesion preventing layer while exhibiting an excellent adhesion preventing property.SOLUTION: The present invention relates to a lid material including at least a base material layer, a transparent resin layer, a hot-melt resin layer and an adhesion preventing layer in turn, wherein a character pattern is expressed on at least one layer of (a) the base material layer, (b) the transparent resin layer, and (c) an intermediate layer which may be formed between both the layers.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a novel container lid material. [Background technology]

[0002] 2. Description of the Related Art In containers for storing foods such as yogurt, jelly, pudding, ice cream, tofu, and chawanmushi, a lid is heat-sealed to the opening of the container to hermetically store the food.

[0003] For such lid materials, a technique has been proposed in which the surface is treated with hydrophobic particles so as to repel the food contents and prevent them from adhering to the lid material.

[0004] For example, a packaging material is known in which hydrophobic oxide fine particles having a primary particle average diameter of 3 to 100 nm are attached to at least a part of the surface of a layer containing a thermoplastic resin (Patent Document 1).

[0005] Furthermore, for example, a content non-adhesive packaging material is known in which a binder layer, a heat seal layer, and a hydrophobic layer are laminated in that order on a base layer, the binder layer is made of a thermosetting resin in which mixed particles having an average particle size of 1 to 100 μm are dispersed, and the mixed particles form an uneven surface on the heat seal layer side, the heat seal layer is made of a thermoplastic resin laminated on the uneven surface, and the hydrophobic layer is made of hydrophobic fine particles having an average particle size of 5 nm to 1 μm and an inorganic binder (Patent Document 2). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2011-93315 A [Patent Document 2] JP 2015-34038 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, in these conventional techniques, the hydrophobic particles cause light scattering, resulting in a cloudy white appearance of the surface-treated surface. Therefore, even if advertisements, information about the contents, etc. are printed on the base of the surface-treated surface (for example, the back surface of the lid), it is difficult to see them. In other words, when a printed substrate is surface-treated with hydrophobic particles as described above, there is a problem that the printed contents become difficult to read depending on the color, darkness, etc. of the print. For this reason, the reality is that the back surface of the lid material surface-treated with hydrophobic particles must be plain.

[0008] In contrast, even if the surface has been subjected to such surface treatment, if it is possible to see through the base, it will be possible to confirm the contents of various letters, colors, patterns, etc. displayed on the back side of the lid material, thereby improving the convenience and design of the lid material.

[0009] Therefore, a main object of the present invention is to provide a container lid material that exhibits excellent adhesion prevention properties while allowing display content such as letters and patterns located below the adhesion prevention layer to be visually recognized. [Means for solving the problem]

[0010] As a result of extensive research into the problems of the prior art, the present inventors discovered that a lid material having a specific configuration can achieve the above object, and thus completed the present invention.

[0011] That is, the present invention relates to the following container lid material. 1. A lid material including at least a base layer, a transparent resin layer, a hot melt resin layer, and an anti-adhesive layer in this order, and having a character pattern on at least one of a) the base layer, b) the transparent resin layer, and c) an intermediate layer that may be formed between the two layers; (1) The transparent resin layer has a thickness of 10 to 40 μm, (2a) the hot melt resin layer contains a wax component, a rosin component, and an ethylene-vinyl acetate copolymer; (2b) The adhesion weight of the hot melt resin layer is 10 to 40 g / m2 in dry weight.2 and (2c) The hot melt resin layer surface has protrusions with a height of 40 to 100 μm formed thereon, (2d) the number of protrusions is 2000 to 5000 per square inch; (3a) the anti-adhesion layer is disposed as an outermost layer; (3b) the adhesion prevention layer contains hydrophobic oxide fine particles having an average primary particle diameter of 3 to 100 nm, (3c) The adhesion amount of the anti-adhesive layer is 0.3 to 1.0 g / m2 in dry weight. 2 and (4) The content of the character pattern can be visually recognized from above the anti-adhesive layer. A container lid material characterized by the above. 2. The container lid material according to item 1, wherein the transparent resin layer contains at least one of polyolefin resin, polyester resin, polyurethane resin, epoxy resin, acrylic resin, and vinyl resin. 3. A packaging product comprising a cup-shaped container filled with contents and the opening of the container sealed with the anti-adhesion layer of the container lid material described in item 1 or 2 facing the inside of the container. 4. The packaging product described in item 3 above, in which an anti-adhesion layer located in the area where the opening of the cup-shaped container and the transparent resin layer of the lid material are thermally bonded to each other is embedded in the transparent resin layer and / or hot melt resin layer during thermal bonding, thereby thermally bonding the transparent resin layer of the lid material to the anti-adhesion layer. Effect of the Invention

[0012] According to the present invention, a lid material can be provided that exhibits excellent adhesion prevention while allowing the display contents such as letters and patterns located below the adhesion prevention layer to be visually recognized. In particular, in the lid material of the present invention, the transparent resin layer and the adhesion prevention layer are configured to exhibit transparency, so that the display contents such as letters and patterns can be accurately visually recognized or read even though the letters and patterns are covered with the transparent resin layer, the hot melt resin layer, and the adhesion prevention layer. At the same time, since the adhesion prevention layer is disposed on the outermost layer (top surface), a high adhesion prevention effect (water repellency) can be exhibited.

[0013] The lid material of the present invention having such characteristics can be used as a lid material for various containers. In particular, it can be suitably used as a lid material used to seal the inside of a container (lid material for airtight containers). Therefore, it can be advantageously used as a lid material for containers that contain, for example, food, cosmetics, medicines, quasi-drugs, etc. [Brief description of the drawings]

[0014] [Figure 1] FIG. 2 is a diagram showing a specific example of the layer structure of the covering material of the present invention. [Diagram 2] FIG. 1 is a schematic cross-sectional view of a container (cup-shaped container) sealed with a lid of the present invention. [Diagram 3] FIG. 2 is a diagram showing the results of observing the surface of a hot melt resin layer (HM) in Example 1. [Figure 4] FIG. 2 is a diagram showing the observation results of a cross section of a laminate in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] 1.Lid material for containers The container lid material of the present invention (lid material of the present invention) comprises at least a base layer, a transparent resin layer, a hot melt resin layer and an adhesion prevention layer in this order, and has a character pattern expressed on at least one layer of a) the base layer, b) the transparent resin layer and c) an intermediate layer that may be formed between the two layers, (1) The transparent resin layer has a thickness of 10 to 40 μm, (2a) the hot melt resin layer contains a wax component, a rosin component, and an ethylene-vinyl acetate copolymer; (2b) The adhesion weight of the hot melt resin layer is 10 to 40 g / m2 in dry weight. 2 and (2c) The hot melt resin layer surface has protrusions with a height of 40 to 100 μm formed thereon, (2d) the number of protrusions is 2000 to 5000 per square inch; (3a) the anti-adhesion layer is disposed as an outermost layer; (3b) the adhesion prevention layer contains hydrophobic oxide fine particles having an average primary particle diameter of 3 to 100 nm, (3c) The adhesion amount of the anti-adhesive layer is 0.3 to 1.0 g / m2 in dry weight. 2 and (4) The content of the character pattern can be visually recognized from above the anti-adhesive layer. It is characterized by:

[0016] FIG. 1 shows an example of the layer structure of the lid material of the present invention. The lid material of the present invention 10 has a substrate layer 11 disposed below, and a printed layer formed as an intermediate layer 12 thereon. Characters or patterns are expressed on the printed layer. The character patterns include, for example, characters (including numbers, symbols, etc.), patterns, pictures, designs, figures, and other displays. More specifically, product names, manufacturer names, bar codes, PR statements, illustrations, logos, trademarks (marks), characters, designs, prize and entry displays, and the like can be mentioned. A transparent resin layer 13 is formed above the printed layer. In FIG. 1, the transparent resin layer 13 is laminated in a state of being in direct contact with the intermediate layer 12.

[0017] 1 shows a form in which an intermediate layer 12, which is a printed layer expressing a character pattern, is introduced, but it is not necessary to form an intermediate layer, and the form is not particularly limited as long as it is a means capable of expressing a character pattern. For example, any form may be used, such as a method of employing a base layer or a transparent protective layer expressing a character pattern, or a method of introducing an intermediate layer with a three-dimensional character pattern.

[0018] In addition, when forming an intermediate layer such as a printed layer, it may be formed on the entire surface of the base layer (so-called solid printing, etc.), or it may be formed on only a part of the surface of the base layer.

[0019] A hot melt resin layer 14 is formed on the surface (upper part) of the transparent resin layer 13. A specific uneven surface is formed on the hot melt resin layer 14. In FIG. 1, the hot melt resin layer 14 is formed so as to be in direct contact with the surface of the transparent resin layer 13.

[0020] An anti-adhesion layer 15 is formed on the surface of the hot melt resin layer 14. More specifically, the anti-adhesion layer 15 is formed by accumulating a plurality of hydrophobic oxide fine particles 15a on the uneven surface of the hot melt resin layer 14. The anti-adhesion layer 15 is disposed as the outermost surface layer of the lid material of the present invention. When the anti-adhesion layer 15 is used as a lid material for a container, it is exposed to a surface that may come into contact with the contents, but even if it comes into contact with the contents, the anti-adhesion layer 15 repels the contents, thereby preventing the contents from adhering (sticking) to the lid material.

[0021] The hydrophobic oxide particles 15a are attached and fixed to the surface of the hot melt resin layer 13 or the transparent resin layer 14 or in contact with other hydrophobic oxide particles. A plurality of hydrophobic oxide particles 15a may be aggregated together to form a three-dimensional network structure. This can provide a higher adhesion prevention effect.

[0022] In the lid material of the present invention, as described above, the character pattern is expressed below the hot melt layer 14, and the display content of the character pattern can be seen through the hot melt layer and the anti-adhesive layer. As shown in FIG. 1, when the lid material is viewed from above A of the anti-adhesive layer, the display content (printed content) of the printing layer, which is the intermediate layer 12, can be seen through the hot melt layer 14 and the transparent resin layer 13. Therefore, for example, if character information is printed on the printing layer, the character information can be read. In particular, in the lid material of the present invention, by adopting the specific layer structure as described above, it is possible to achieve an excellent anti-adhesive effect and obtain higher visibility, even though the character pattern is covered by the anti-adhesive layer, the hot melt resin layer, and the transparent resin layer.

[0023] The thickness of the lid material of the present invention can be appropriately set depending on, for example, the type of contents, the shape of the container, etc., and can be, for example, in the range of about 70 to 200 μm, but is not limited thereto. Each layer will be described in more detail below.

[0024] Base material layer In the present invention, the base layer functions as a core material for the lid material, in particular by imparting stiffness to the lid material, imparting durability to the lid material against breakage, etc., and by providing strength to the lid material so that the lid material will not be accidentally broken when it is peeled off while it is adhered to the container.

[0025] In addition, in cases where it is undesirable for the contents filled in the container to be exposed to light, air, etc., the base material is provided with a layer that has the effect of suppressing the transmission of light, preventing the intrusion of outside air, or suppressing the transmission of gas, thereby preventing the smell of the contents from leaking out of the container.

[0026] The material of the substrate layer is not particularly limited as long as it has the above-mentioned functions, and various materials such as plastics, rubber, metal, glass, ceramics, paper, etc. can be used. Therefore, as a material for forming the substrate layer, for example, paper, synthetic paper, resin film, resin film with a vapor deposition layer, synthetic resin plate, aluminum foil or other metal foil, metal plate, woven fabric, nonwoven fabric, leather, synthetic leather, wood, glass plate, etc., alone or composite materials or laminate materials thereof can be suitably used. Among these, it is preferable to use aluminum foil or a resin film with a vapor deposition layer, since it is possible to obtain a predetermined strength while preventing the transmission of light or gas.

[0027] The thickness of the base layer is not particularly limited, but is usually about 7 to 30 μm, and preferably 12 to 20 μm.

[0028] transparent resin layer The transparent resin layer mainly plays the roles of a) ensuring cushioning as a base for the anti-adhesive layer in order to laminate the anti-adhesive layer on the base layer, and b) imparting adhesion to the hot melt resin. In addition, along with these functions, it is a layer that can also contribute to the sealing property with the container as a lid material.

[0029] The transparent resin layer contains a resin component, and preferably contains a thermoplastic resin having thermal adhesiveness as the resin component, which allows the transparent resin layer to function as a thermal adhesive layer, thereby firmly fixing the adhesion prevention layer (particularly the hydrophobic oxide fine particles) to the substrate layer as described above.

[0030] From the above viewpoint, the thermoplastic resin constituting the transparent resin layer is not limited as long as it is a resin having thermal adhesiveness, and examples of the adhesives include polyolefin resins, polyester resins, polyurethane resins, epoxy resins, acrylic resins, vinyl resins, etc. More specifically, a) polyolefin resins such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear (linear) low-density polyethylene, polypropylene, ethylene-vinyl acetate copolymer, ionomer resin, ethylene-acrylic acid copolymer, vinyl chloride-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, ethylene-methacrylic acid copolymer, ethylene-methyl methacrylate copolymer, ethylene-propylene copolymer, methyl pentaethylene polymer, polybutene polymer, polyethylene, or polypropylene, b) acid-modified polyolefin resins obtained by modifying these polyolefin resins with unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic acid, maleic anhydride, fumaric acid, and itaconic acid, and c) polyvinyl acetate resins, poly(meth)acrylic resins, polyacrylonitrile resins, polyvinyl chloride resins, etc. may be mentioned. Other examples include blend resins of these, copolymers containing combinations of monomers constituting these, and modified resins.

[0031] Among these, in the present invention, polyolefin resins are preferred, and among these, polyethylene resins are more preferred. More specifically, examples include polyethylene resins such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear (linear) low-density polyethylene, as well as ethylene copolymers such as ethylene-vinyl acetate copolymer resins. Among these, in the present invention, it is preferred to employ polyethylene resins, and in particular, low-density polyethylene resins can be suitably employed.

[0032] The method for forming the transparent resin layer is not particularly limited, and examples thereof include a) a method of applying and drying a solution in which a transparent resin is dissolved in a solvent or a dispersion in which a transparent resin is dispersed in a solvent, b) a method of extruding and applying a molten transparent resin, followed by cooling and solidifying it, and c) a method of laminating a transparent resin film with or without an adhesive. In order to improve adhesion to the substrate, an adhesive (anchor coating agent) may be applied to the substrate layer in an amount of 0.01 to 1.0 g / m as necessary. 2 It is preferable to coat the coating layer to a certain extent.

[0033] When forming an adhesive layer, the adhesive that can be used is not limited as long as it can be used for food applications, and for example, a laminating adhesive can be suitably used. Examples of the components of the laminating adhesive include polyester adhesives, polyether adhesives, and polyurethane adhesives. The properties of the adhesive are also not limited, and for example, any of solvent-based, solventless, and water-based adhesives can be used. In addition, the film can be coated with a coating liquid containing hydrophobic particles as necessary, dried, and then the opposite side to the coated side can be laminated to another substrate.

[0034] The thickness of the transparent resin layer is preferably about 10 to 40 μm in terms of sealing with the container and light transmission. If the thickness is less than 10 μm, the cushioning effect during sealing of the container is weak, and the seal balance is poor, which makes it easy for sealing defects to occur. If the thickness exceeds 40 μm, the color tone of the surface on the back side of the lid becomes cloudy, making it difficult to clearly see the printed layer.

[0035] The content of the thermoplastic resin in the transparent resin layer may be sufficient as long as it can exhibit the above-mentioned cushioning properties, and is usually about 90 to 100% by mass, but is not limited thereto.

[0036] In addition, other additives may be appropriately blended into the transparent resin layer as necessary within the range that does not impair the effects of the present invention, such as dispersants, colorants, anti-settling agents, viscosity modifiers, defoamers, fillers, antistatic agents, ultraviolet absorbers, and oxygen absorbers.

[0037] In the present invention, it is preferable that the transparent resin layer does not contain particles (hereinafter referred to as "filler particles") having a particle size that gives the surface of the transparent resin layer unevenness. In this case, the size of the filler particles is large enough to give the surface of the transparent resin layer unevenness derived from the filler particles, and the average particle size (measured by a laser diffraction particle size distribution meter) is usually 10 to 40 μm, particularly 12 to 30 μm.

[0038] Hot melt resin layer The hot melt resin layer contributes to the thermal adhesion when the lid material of the present invention is joined to the container, and also plays a role in ensuring the ease of opening the lid material of the present invention joined to the container.

[0039] The hot melt resin layer contains a wax component, a rosin component, and an ethylene-vinyl acetate copolymer.

[0040] The wax component is not particularly limited, and examples thereof include petroleum waxes such as paraffin wax, natural waxes such as carnauba wax and palm wax, and synthetic waxes such as polyethylene and polypropylene. The content of the wax component in the hot melt resin layer is usually about 20 to 80% by weight, but is not limited thereto.

[0041] The rosin component is not limited, and examples thereof include various rosins such as gum rosin, wood rosin, etc. The content of the rosin component in the hot melt resin layer is usually about 0.5 to 30% by weight, but is not limited thereto.

[0042] The ethylene-vinyl acetate copolymer may be any copolymer of ethylene and vinyl acetate, and may be of various grades. The content of the ethylene-vinyl acetate copolymer in the hot melt resin layer is usually about 20 to 50% by weight, but is not limited thereto.

[0043] In addition to these three components, the hot melt resin layer may contain other additives within the range that does not impair the effects of the present invention. Examples of additives include the various additives described in the explanation of the transparent resin layer.

[0044] In the present invention, the hot melt resin layer can be formed using a composition containing these components. As such a composition, a known or commercially available hot melt adhesive can be used. For example, the hot melt adhesive is applied in a molten state and then cooled and solidified. If hydrophobic oxide fine particles are then applied, the hydrophobic oxide fine particles can be attached directly to the thermal adhesive layer, which makes it easy to continuously produce the packaging material of the present invention.

[0045] The hot melt resin layer has protrusions with a height of 40 to 100 μm formed on its surface (the anti-adhesion layer side), and the density (number) of the protrusions is 2000 to 5000 per square inch. This makes it possible to more firmly fix the hydrophobic oxide particles in the anti-adhesion layer, and also makes it easier for the hydrophobic oxide particles to be embedded during thermal adhesion, resulting in a higher sealability.

[0046] The shape of the protrusions is not particularly limited, and may be, for example, substantially conical, substantially pyramidal, substantially cylindrical, substantially prismatic, substantially hemispherical, etc. Furthermore, one or more of these shapes may be included.

[0047] The height of the protrusions is the height from the transparent resin layer, which is the base, to the top of the protrusions, and is usually in the range of 40 to 100 μm, and is preferably 50 to 80 μm. As described above, the density of the protrusions is usually in the range of 2000 to 5000 pieces / square inch, and is preferably 3000 to 4000 pieces / square inch. By setting it in such a range, good adhesion prevention can be achieved. If the height of the protrusions is less than 40 μm or the density is less than 2000 pieces / square inch, the hydrophobic oxide fine particles are weakly fixed and easily detached during transportation, etc., making it difficult to maintain good adhesion prevention. On the other hand, if the height of the protrusions exceeds 100 μm or the density exceeds 5000 pieces / square inch, the color tone of the surface on the back side of the lid becomes cloudy, and the printed layer is difficult to clearly see.

[0048] In the present invention, the height of the protrusions can be confirmed by a method of cutting a sample with a cutting machine such as a microtome to produce a smooth cross section at the apex of the protrusions, and observing and measuring the length of the cross section under a microscope. The density of the protrusions can be measured by observing the sample under a microscope so that the entire field of view is filled with the sample, counting the number of protrusions in the field of view, and converting this into the number per unit area (total number / area of ​​field of view).

[0049] In the present invention, protrusions having a height of less than 40 μm or protrusions having a height of more than 100 μm may be included as long as the effects of the present invention are not hindered.

[0050] The amount of hot melt resin layer applied is 10 to 40 g / m2 in dry weight. 2 Approximately 15 to 25 g / m 2 The coating amount is preferably 10 g / m 2 If the adhesion amount is less than 40 g / m, the hydrophobic oxide particles cannot be embedded in the thermal adhesive layer, which hinders sealing with the container. 2 If it exceeds this value, the color tone of the surface on the back side of the lid becomes cloudy and the printed layer becomes difficult to clearly see.

[0051] The method for forming the hot melt resin layer is not particularly limited as long as the above-mentioned predetermined protrusions are formed. For example, the hot melt resin layer having the above-mentioned protrusions can be suitably formed by applying the hot melt resin in a molten state using a gravure plate having a predetermined surface unevenness, and then cooling and solidifying the hot melt resin.

[0052] Anti-adhesive layer The anti-adhesion layer is a layer provided on the outermost surface of the back of the lid of the container lid material. In other words, it is a layer that can come into contact with the contents when the container lid material is adhered to the container. The anti-adhesion layer contains hydrophobic oxide fine particles. The anti-adhesion layer only needs to contain hydrophobic oxide fine particles, and may also contain a binder resin that bonds the hydrophobic oxide fine particles together. Preferably, a part of the anti-adhesion layer is embedded in the thermoplastic resin in the transparent resin layer, and bonds the hydrophobic oxide fine particles together.

[0053] The hydrophobic oxide fine particles are not particularly limited as long as they have hydrophobicity, and may be those that have been hydrophobized by surface treatment. For example, hydrophilic oxide fine particles may be surface-treated with a silane coupling agent or the like to make the surface hydrophobic. The type of oxide is also not limited as long as it has hydrophobicity. For example, at least one of silica (silicon dioxide), alumina, titania, etc. may be used. These may be publicly known or commercially available. For example, silica may be products such as "AEROSIL R972", "AEROSIL R972V", "AEROSIL R972CF", "AEROSIL R974", "AEROSIL RX200", "AEROSIL RY200" (all manufactured by Nippon Aerosil Co., Ltd.), "AEROSIL R202", "AEROSIL R805", "AEROSIL R812", "AEROSIL R812S" (all manufactured by Evonik Degussa). An example of titania is AEROXIDE TiO2T805 (manufactured by Evonik Degussa), etc. An example of alumina is AEROXIDE Alu C (manufactured by Evonik Degussa), etc., which is a fine particle whose particle surface has been made hydrophobic by treating it with a silane coupling agent.

[0054] Among these, hydrophobic silica fine particles can be preferably used. In particular, hydrophobic silica fine particles having trimethylsilyl groups on the surface are preferred in that they provide better adhesion prevention. Examples of corresponding commercially available products include the aforementioned "AEROSIL R812" and "AEROSIL R812S" (both manufactured by Evonik Degussa).

[0055] The hydrophobic oxide fine particles contained in the adhesion prevention layer have a primary average particle diameter of 3 to 100 nm, and preferably 5 to 20 nm. By setting the primary particle average diameter within the above range, the hydrophobic oxide fine particles are in a moderately aggregated state, and gas such as air can be held in the voids in the aggregate, resulting in excellent adhesion prevention. In other words, this aggregated state is maintained even after adhesion to the transparent resin layer, so that excellent adhesion prevention can be achieved.

[0056] In the present invention, the average primary particle diameter can be measured using a scanning electron microscope (FE-SEM), and when the resolution of the scanning electron microscope is low, it may be measured using other electron microscopes such as a transmission electron microscope in combination. Specifically, when the particle shape is spherical, the diameter is regarded as the diameter, and when the particle shape is non-spherical, the average of the longest and shortest diameters is regarded as the diameter, and the average of the diameters of 20 particles randomly selected by observation using a scanning electron microscope or the like is regarded as the average primary particle diameter.

[0057] The amount of hydrophobic oxide particles attached to the transparent resin layer (weight after drying) is 0.3 to 1.0 g / m 2 By setting the thickness within the above range, it is possible to obtain a more excellent non-adhesive property for a long period of time, and it is more advantageous in terms of preventing the hydrophobic oxide fine particles from falling off, costs, etc. It is preferable that the hydrophobic oxide fine particles adhered to the thermal adhesive layer form a porous layer having a three-dimensional network structure.

[0058] The hydrophobic oxide fine particles may be attached to the entire surface of the transparent resin layer (the entire surface of the surface opposite to the substrate layer side), or may be attached to the area excluding the area where the transparent resin layer is thermally bonded (so-called bonding area). In the present invention, even if the hydrophobic oxide fine particles are attached to the entire surface of the transparent resin layer, most or all of the hydrophobic oxide fine particles present on the area where the transparent resin layer is thermally bonded are embedded in the transparent resin layer, so that thermal bonding is not hindered, and it is preferable that the hydrophobic oxide fine particles are attached to the entire surface of the transparent resin layer from the viewpoint of industrial production.

[0059] The thickness of the adhesion prevention layer can be appropriately set within the range of the above-mentioned adhesion amount, and can be, for example, about 0.1 to 5 μm, but is not limited thereto.

[0060] The method for forming the anti-adhesion layer is not particularly limited, but can be suitably carried out by a method including a step of applying a dispersion liquid in which hydrophobic oxide microparticles are dispersed in a solvent to a part or all of the surface of the transparent resin layer, and drying the applied liquid.

[0061] The solvent used in the dispersion is not particularly limited, and one or more solvents that are commonly used in food production, such as water and ethanol, can be used.

[0062] The content of the hydrophobic oxide fine particles in the dispersion is not particularly limited, but it is generally preferable to set it appropriately within the range of about 5 to 200 g / L (liter).

[0063] Furthermore, the dispersion may contain, as necessary, a dispersant, a colorant, an anti-settling agent, a viscosity adjuster, a binder, a defoaming agent, and the like, within the range that does not impair the effects of the present invention.

[0064] The method for applying the dispersion onto the transparent resin layer is not particularly limited, and any known method can be appropriately adopted, such as roll coating, various gravure coatings, bar coating, doctor blade coating, comma coater, brush coating, etc. If the hydrophobic oxide fine particles are mixed in a dispersion medium, they can be applied more uniformly.

[0065] The coating amount (weight after drying) can be appropriately set depending on the desired water repellency or oil repellency, but is usually 0.3 to 1.0 g / m 2 Approximately 0.4 to 0.6 g / m 2 By setting the content within the above range, a porous layer made of anti-adhesion particles can be more reliably formed, and as a result, more excellent non-adhesion properties can be obtained for a long period of time, and further advantages are obtained in terms of preventing the fine particles from falling off, costs, etc.

[0066] After coating, the coated surface is dried to obtain a film with the adhesion-preventive particles adhered to the resin substrate film. The drying method is not particularly limited, and may be either natural drying or heat drying. When heat drying is performed, the temperature is usually about 60 to 190°C, and preferably 80 to 150°C. The heating time may be appropriately set depending on the heating temperature, etc., but is usually about 3 to 30 seconds.

[0067] The water repellency of the formed adhesion preventing layer is preferably such that the contact angle with pure water (25° C.) is usually 140° or more, particularly 150° or more.

[0068] Other layers In the lid material of the present invention, other layers may be formed as long as they do not impede the effects of the present invention. For example, an adhesive layer may be interposed between the layers. In addition, for example, a printed layer, an overcoat layer, a clear layer, etc. may be formed on the surface opposite to the transparent resin layer of the substrate (i.e., the surface on the side where the lid material is exposed to the outside).

[0069] Expression of character design In the lid material of the present invention, a character pattern is expressed on at least one layer of a) the base material layer, b) the transparent resin layer, and c) an intermediate layer that may be formed between the two layers. As described above, in the lid material of the present invention, the character pattern is expressed on the lower side of the hot melt resin layer (the side opposite to the anti-adhesive layer), and the displayed content can be seen through. In the conventional lid material, characters, patterns, etc. are applied to the front surface (outside), but since an anti-adhesive layer is formed on the back surface, even if a character pattern is displayed, it is not visible or difficult to see, so printing on the back surface has been avoided. In contrast, in the lid material of the present invention, even if an anti-adhesive layer is formed on the outermost layer, the character pattern arranged on the lower layer can be seen through, so it is possible to freely apply character patterns and other designs to the back surface of the lid material.

[0070] The method of expressing the character pattern may be any method as long as the display content can be seen from above the adhesion prevention layer as shown in Fig. 1. For example, there may be mentioned, but are not limited to, a) a method of introducing a printed layer as an intermediate layer, b) a method of forming a character pattern three-dimensionally by unevenness, c) a method of forming a base layer, a transparent resin layer or an intermediate layer using a film on which a character pattern is previously expressed during production, and d) a method of laminating a member on which a character pattern is expressed. In addition, each of these methods may be used alone or in combination of two or more.

[0071] In the above method a), the printing layer can be formed by printing ink in a predetermined pattern using a known printing method such as gravure printing, flexographic printing, inkjet printing, silk screen printing, etc. Alternatively, the printing layer can be formed by transferring the printing layer using a transfer film, etc. In this way, the printing layer can be formed by printing the surface of the base layer using ink, a transfer film, etc.

[0072] When applying a printing layer, the color is not limited, and various colors of ink such as white, black, red, green, yellow, etc. can be used as appropriate. In particular, when the contents to be filled in the container are foods, etc., it is preferable to use edible ink in that higher safety can be ensured. In addition, the ink may be either oil-based ink or water-based ink.

[0073] In the above (b), for example, examples of the method of forming a character pattern three-dimensionally by unevenness include (b1) a method of forming a character pattern by engraving a base layer, a transparent resin layer, or an intermediate layer, and (b2) a method of forming a base layer, a transparent resin layer, or an intermediate layer using a film on which a character pattern has been formed three-dimensionally by unevenness in advance. The method of (b1) above is not particularly limited, and may be either engraving by laser (non-contact type) or engraving by various engraving machines (contact type). The method of (b2) above is also not limited, and may be, for example, a method of molding by press molding using a mold on which a character pattern for transfer is printed. In the above (b), the formation of unevenness may be performed on either one side or both sides of each layer. In addition, when performing on one side, it may be on either the side on which the transparent resin layer is laminated or the opposite side.

[0074] In the above (c), examples include (c1) a method of forming a base layer, a transparent resin layer, or an intermediate layer using a film having a component expressing a character pattern incorporated therein (for example, a plate or the like having a specific character pattern embedded therein), and (c2) a method of forming a base layer, a transparent resin layer, or an intermediate layer using a film on which a pattern, character, or the like is drawn using a colored resin.

[0075] In the above (d), for example, a method of laminating a member expressing a character design onto a base layer, a transparent resin layer or an intermediate layer can be mentioned.

[0076] In the lid material of the present invention, a text pattern may be displayed on the other side of the base layer (the outer side of the container). The same printing layer as that of a known lid material may be used for this purpose.

[0077] 2. Use of container lid materials The lid material of the present invention can be used as a lid for various containers. More specifically, it is used to close the opening of a container with the anti-adhesion layer on the outermost surface of the lid material of the present invention disposed on the inside of the container. That is, the lid material of the present invention has a substrate (sheet-like substrate), and both sides of the substrate face the outside and the inside of the container when the lid material for containers is used as a lid for the container.

[0078] FIG. 2 shows a packaged product 20 in which the opening of a cup-shaped container 17 filled with contents 16 is closed by the lid material 10 of the present invention in FIG. 1. The flange portion 17a of the opening of the cup-shaped container 17 and the transparent resin layer 13 and hot melt resin layer of the lid material are bonded by thermal adhesion (heat sealing), thereby realizing sealing of the contents 16. In this case, before thermal bonding, the hydrophobic oxide particles 15a of the adhesion prevention layer 15 are laminated on the thermally bonded area of ​​the lid material of the present invention, but the hydrophobic oxide particles are embedded in the transparent resin layer 13 and / or the hot melt resin layer 14 during thermal bonding. This realizes particularly strong bonding between the transparent resin layer 13 and the container opening. Since the hydrophobic oxide particles 15a are exposed in the area other than the thermally bonded area, when food or the like is contained as the contents, the contents are less likely to adhere to the lid material even if the contents come into contact with the lid material.

[0079] 2, the surface facing the inside of the container is provided with, in order from the base material layer 11, an intermediate layer (printed layer) 12, a transparent resin layer 13, a hot melt resin layer 14, and an anti-adhesion layer 15. If necessary, the surface facing the outside of the container may be appropriately provided with, for example, a second base material layer, a printed layer, a protective layer for protecting the printed layer, and the like (not shown).

[0080] In this case, the printing layer 12 provided on the surface of the base material layer 11 on the side having the adhesion prevention layer 15 is also called the lid back printing, and the printing applied to the other surface is also called the front printing. In general, information about the contents to be filled in the container (for example, product name, logo, ingredients, expiration date, image of the contents, barcode, etc.) is printed on the front printing. In general lid back printing that does not have a function to prevent the contents from adhering may be printed with information about the product, campaign information, advertisements, etc., but in the conventional technology, when the back of the lid has a function to prevent the contents from adhering, the back printing of the lid is avoided because the structure of the adhesion prevention function of the surface causes light to be diffused and becomes white and dull, making it difficult to see. In contrast, in the lid material of the present invention, as shown in FIG. 1, for example, even when viewed from the A direction, the display content of the printing layer 12 can be seen (see-through) through the adhesion prevention layer 15 and the transparent resin layer 13, so that the display content can be reliably and easily understood. As such, container lid materials that have a function to prevent contents from adhering but do not have a lid back print, and container lid materials that have a lid back print but do not have a function to prevent contents from adhering, are both well known, but container lid materials that have a lid back print and also have a function to prevent contents from adhering originally require conflicting conditions in the manufacture of container lid materials, and the lid material of the present invention achieves both.

[0081] In FIG. 2, a cup-shaped container is shown, but the container shape is not limited as long as the lid material of the present invention can be applied, and it can be applied to any shape such as a tray shape or a bottle shape.

[0082] The contents to be filled in the container are not particularly limited, and may be any of foods such as yogurt, pudding, and ice cream, cosmetics, medicines, etc. The nature of the contents is also not limited, and may be applied to, for example, solid materials as well as fluid materials. The contents may be either gel-like or non-gel-like. Furthermore, the contents may be a material containing at least one of water and oil (oils and fats), but contents containing water in particular can be preferably used. EXAMPLES

[0083] The features of the present invention will be described in more detail below with reference to examples and comparative examples, although the scope of the present invention is not limited to the examples.

[0084] Example 1 A polyurethane-based dry lamination adhesive (weight after drying: 3.5 g / m) was applied to one side of an aluminum foil (1N30, soft foil; abbreviated as AL) with a thickness of 15 μm. 2 A 12 μm thick polyethylene terephthalate film (abbreviated as PET) with reverse printing (abbreviated as PRINT) was laminated using a 12 μm thick polyethylene terephthalate film (abbreviated as D) to create a base layer. The aluminum surface of this base layer was printed. The print was a two-dimensional barcode design to make it easier to compare visibility. An anchor coat (main component: polyester resin; abbreviated as AC) was applied on top of this printed layer, and low-density polyethylene resin (abbreviated as LDPE) was extrusion-laminated to a film thickness of 20 μm. Furthermore, a hot melt agent (35 parts by weight of wax, 35 parts by weight of rosin, and 30 parts by weight of ethylene-vinyl acetate copolymer; abbreviated as HM) was applied on top of the low-density polyethylene at a weight of 20 g / m2. 2 The resulting laminate was gravure hot melt coated to a thickness of 50 μm and approximately 3,500 particles / square inch. This resulted in a laminate having a structure of "PET / printing / D / AL / printing / AC / LDPE / HM." Here, the surface of the hot melt resin layer (HM) of the obtained laminate was observed. The surface was observed with a scanning electron microscope, and the number of protrusions within the field of view was counted, and the density of the protrusions was calculated by dividing the number by the area of ​​the field of view. A micrograph of the surface is shown in Figure 3. A cross section of the laminate was also cut out, and the height of all the protrusions on that cross section was measured. A micrograph of the cross section is shown in Figure 4. The density and height of the protrusions are shown in Table 1 (similar measurements were also made in the following Examples and Comparative Examples, and the results are also shown in Table 1). Next, as an adhesion prevention layer, hydrophobic oxide particles (product name "AEROSIL R812S" manufactured by Evonik Degussa, BET specific surface area: 220 m 2A coating solution was prepared by dispersing 5 g of 100 mL of ethanol (5 g of 100% ethanol, average primary particle diameter: 7 nm) in the transparent resin layer of the laminate, and applying the coating solution to the surface of the transparent resin layer of the laminate in an amount of 0.5 g / m2 after drying. 2 After applying the coating by a bar coating method so that the ethanol had evaporated, the coating was dried at 100° C. for about 10 seconds to evaporate the ethanol, thereby obtaining a container lid material sample.

[0085] Example 2 Low density polyethylene film thickness 10μm, hot melt agent weight 10g / m 2 A container lid material sample was obtained in the same manner as in Example 1, except that the number of particles was 40 μm, the thickness was 40 μm, and the number of particles was about 2000 per square inch.

[0086] Example 3 Low density polyethylene film thickness 40μm, hot melt agent weight 40g / m 2 A container lid material sample was obtained in the same manner as in Example 1, except that the number of particles was 100 μm, the thickness was 100 μm, and the number of particles was about 5,000 per square inch.

[0087] Comparative Example 1 A container lid material sample was produced in the same manner as in Example 1, except that no adhesion preventing layer was provided.

[0088] Comparative Example 2 The coating amount of hydrophobic oxide particles for the adhesion prevention layer was 1.2 g / m2 after drying. 2 A container lid material sample was obtained in the same manner as in Example 1, except that the thickness was changed to 100 μm.

[0089] Comparative Example 3 Low density polyethylene film thickness 9μm, hot melt agent weight 8g / m 2 A container lid material sample was obtained in the same manner as in Example 1, except that the number of particles was 20 μm, the thickness was 20 μm, and the number of particles was about 1,800 per square inch.

[0090] Comparative Example 4 Low density polyethylene film thickness 45μm, hot melt agent weight 50g / m2 A container lid material sample was obtained in the same manner as in Example 1, except that the number of particles was 110 μm, the thickness was 110 μm, and the number of particles was about 5,500 per square inch.

[0091] Comparative Example 5 A container lid material sample was obtained in the same manner as in Example 1, except that the hydrophobic oxide fine particles in the adhesion prevention layer were changed to Silohorbic-100 (manufactured by Fuji Silysia Chemical), which is hydrophobic silica particles having an average primary particle diameter of 2.7 μm.

[0092] Test Example 1 (Visibility of the Print on the Back of the Lid) The visibility of the print on the back of the lid was evaluated for the samples obtained in each of the Examples and Comparative Examples. The readability of the printed two-dimensional barcode was evaluated using the camera of a smartphone (Samsung Electronics Galaxy SC-04J). The evaluation method was to bring the camera close to the smartphone at a distance of 10 to 15 cm so that the entire two-dimensional barcode was displayed in the entire field of view of the smartphone through the camera, and samples that could be read immediately were marked as "good", and samples that took several seconds to read or were unreadable were marked as "bad". The evaluation results are shown in Table 1.

[0093] Test Example 2 (Seal Strength) Packages were produced using lids cut from each packaging material into the shape of the lid (75 mm diameter circle with tab). Specifically, packages were produced by heat sealing the lids onto the flanges of flanged paper / polyethylene containers (flange width 3 mm, flange outer diameter 70 mm, height approximately 55 mm, internal volume approximately 130 cm3, paper approximately 300 μm thick coated with 100 μm polyethylene and molded so that the polyethylene was on the inside of the container). The heat sealing conditions were a temperature of 160°C and a pressure of 1 kg / cm. 2 It was set to one second. The tab of the lid material on each package was pulled at a speed of 100 mm / min in a direction at an elevation angle of 45 degrees from the opening start point, and the maximum load at the time of opening was taken as the seal strength (N). Measurements were performed at n=6 points for each package, and the average value was calculated. Samples that showed good openability with an average value of 10.0 to 15.0 N / CUP were marked as "good", and samples that showed a weak seal strength with an average value of less than 5.0 N / CUP or a seal strength exceeding 15.0 N / CUP were marked as "bad".

[0094] Test Example 3 (Anti-adhesion properties) Heat sealing conditions: temperature 160℃ and pressure 1kg / cm 2 From the above, 180℃ and pressure 3kg / cm 2 A container seal sample was obtained in the same manner as in Test Example 2, except that the above-mentioned procedure was followed. Each package was vibrated for 1 minute 40 seconds (10Hz-10 seconds, 15Hz-10 seconds, 20Hz-10 seconds, 25Hz-10 seconds, 30Hz-10 seconds, repeated twice, with 2.2mm amplitude (vertical direction) and acceleration of about 2G) using a vibration tester (IDEX Corporation TRANSPORTATION TESTER BF-30U). The lid was then opened with fingers and the amount of yogurt attached to each lid (adhesion area) was visually judged. On the surface (anti-adhesion layer) that comes into contact with the contents, samples with an adhesion area of ​​0% to less than 10% were marked as "Good", samples with an adhesion area of ​​10% to less than 30% were marked as "Good", and samples with an adhesion area of ​​30% to less than 100% were marked as "Poor". The evaluation results are shown in Table 1.

[0095] [Table 1]

[0096] As is clear from the results in Table 1, the container lid material of the present invention has the function of preventing the contents from sticking to the back of the lid, while also making it possible to clearly see the printed content of the printing layer, regardless of the color or darkness of the printing layer on the back of the lid.

Claims

1. A lid material including at least a base layer, a transparent resin layer, a hot melt resin layer, and an anti-adhesive layer in this order, and a character pattern is expressed on at least one layer of a) the base layer, b) the transparent resin layer, and c) an intermediate layer that may be formed between the two layers, (1) The transparent resin layer has a thickness of 10 to 40 μm, (2a) the hot melt resin layer contains a wax component, a rosin component, and an ethylene-vinyl acetate copolymer; (2b) The amount of the hot melt resin layer attached is 10 to 40 g / m2 in terms of dry weight. 2 and (2c) protrusions having a height of 40 to 100 μm are formed on the surface of the hot melt resin layer; (2d) the number of protrusions is 2,000 to 5,000 per square inch; (3a) the anti-adhesion layer is disposed as an outermost layer; (3b) the adhesion prevention layer contains hydrophobic oxide fine particles having an average primary particle size of 3 to 100 nm; (3c) The adhesion amount of the adhesion preventing layer is 0.3 to 1.0 g / m2 in terms of dry weight. 2 and (3d) the hydrophobic oxide fine particles aggregate with each other to form a three-dimensional network structure, and the three-dimensional network structure is a porous layer; (4) The content of the character pattern can be visually confirmed from above the anti-adhesive layer. A container lid material characterized by the above.

2. 2. The container lid material according to claim 1, wherein the transparent resin layer contains at least one of a polyolefin resin, a polyester resin, a polyurethane resin, an epoxy resin, an acrylic resin, and a vinyl resin.

3. 3. A packaged product comprising a cup-shaped container filled with a content, the opening of which is sealed with the anti-adhesion layer of the container lid material according to claim 1 or 2 facing the inside of the container.

4. The packaging product described in claim 3, wherein an anti-adhesion layer located on the area where the opening of the cup-shaped container and the transparent resin layer of the lid material are thermally bonded to each other is embedded in the transparent resin layer and / or the hot melt resin layer during thermal bonding, thereby thermally bonding the transparent resin layer of the lid material to the anti-adhesion layer.

Citation Information

Patent Citations

  • Laminate and packaging material

    JP2011093315A

  • Content sticking preventive lid material

    JP2013159344A

  • Lid member and method of manufacturing the same

    JP2014156256A

  • Content non-adhesive packaging material

    JP2015034038A

  • Packaging material and packaging container

    WO2016190262A1